2010
DOI: 10.1007/s12013-010-9091-2
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin Suppresses Phorbol 12-myristate 13-acetate-Induced MMP-2/MMP-9 Expressions via αvβ3 Integrin/FAK/ERK and NF-κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells

Abstract: The purpose of this study is to investigate the anti-metastatic effect of alpha-mangostin on phorbol 12-myristate 13-acetate (PMA)-induced matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) expressions in A549 human lung adenocarcinoma cells. Firstly, alpha-mangostin could inhibit PMA-induced abilities of the adhesion, invasion, and migration. Data also showed alpha-mangostin could inhibit the activation of alphavbeta3 integrin, focal adhesion kinase (FAK), and extracellular signal-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 49 publications
4
53
0
1
Order By: Relevance
“…This inhibition is also expected to have an impact on the mechanisms of tumor metastasis mediated by the FAK protein. This result is supported by Shih, et al [19], who have shown that α-mangostin can inhibit αvβ3 integrin, focal adhesion kinase (FAK), ERK1/2, MMP-2 and MMP-9.…”
Section: Figuresupporting
confidence: 59%
“…This inhibition is also expected to have an impact on the mechanisms of tumor metastasis mediated by the FAK protein. This result is supported by Shih, et al [19], who have shown that α-mangostin can inhibit αvβ3 integrin, focal adhesion kinase (FAK), ERK1/2, MMP-2 and MMP-9.…”
Section: Figuresupporting
confidence: 59%
“…141 Treatment with α-mangostin in vitro has been shown to decrease MMP2 and MMP9 expression and to inhibit HNSCC growth in a concentration-dependent manner, possibly through a JNK and ERK1/2 signaling pathway. 142,143 Also, proteasome inhibitors, including ALLN and lactacystin, caused suppression of TNFα-induced migration of OSCC cells, via interruption of …”
Section: Targeting Mmp Catalytic Activitymentioning
confidence: 99%
“…Excessive degradation of extracellular matrix mediated by proteolytic enzymes such as activated MMPs, especially MMP-2 and MMP-9, is one of the hallmarks of tumor invasion and migration. α-MG could downregulate the expressions of MMP-2 and MMP-9 in a concentration-dependent manner, thereby blocking the invasion and metastasis of various cancers, including skin cancer [105], head and neck squamous cell carcinoma [106], lung adenocarcinoma [107], prostate carcinoma [108], and pancreatic cancer [109]. The underlying mechanisms were closely associated with the suppression of upstream kinase(s), such as MAPK family members (ERK, JNK, and p38) and PI3K/Akt, and the inactivation of downstream transcription factor(s), such as NF-κB and AP-1.…”
Section: Inhibition Of Migration Invasion Metastasismentioning
confidence: 99%
“…The underlying mechanisms were closely associated with the suppression of upstream kinase(s), such as MAPK family members (ERK, JNK, and p38) and PI3K/Akt, and the inactivation of downstream transcription factor(s), such as NF-κB and AP-1. In addition, the study performed in PMA-treated highly metastatic human lung adenocarcinoma A549 cells further explored the upstream regulators, a new finding from which ERK1/2 inhibition and NF-κB inactivation emerged through impeding the activation of αvβ3 integrin and phosphorylation of FAK [107]. TIMPs occur naturally within the extracellular matrix, which inhibit both proand active MMPs and provide a homeostatic environment in the matrix.…”
Section: Inhibition Of Migration Invasion Metastasismentioning
confidence: 99%